Evaluation of needle movement effect on root canal irrigation using a computational fluid dynamics model - Hu, Shanshan (Biomed Eng Online, 2019)
BACKGROUND: Irrigation is considered to be a critical part of root canal treatment. However, little is known about the effect of needle movement on the irrigation process. Therefore, this study aimed to investigate the influence of the syringe and needle movement on root canal irrigation using a three-dimensional computational fluid dynamics (CFD) numerical model. METHODS: The CFD codes Flow-3D was adopted to simulate the root canal irrigation process with the syringe and needle moving up and down in motions at different amplitudes and frequencies. One stationary needle was adopted to allow comparison with the needles in up-and-down motions. Six cases where the needles were moving up and down with different amplitudes and frequencies were used to investigate the relationships between the motion of needle and irrigation efficacy. RESULTS: The stationary needle gained relatively higher flow velocity and apical pressure all through the irrigation process, while the needles in constant up-and-down motions exhibited lower mean flow velocity and apical pressure. The larger the amplitude, the less mean flow velocity and apical pressure were developed. In addition, the needles moving with different frequencies were similar in the terms of irrigant replacement and apical pressure. CONCLUSIONS: To avoid periapical extrusion accidents while obtaining adequate irrigant replacement, the needle should be moving up and down with a moderate amplitude during manual root canal irrigation; and the motion frequency was not highly relevant in terms of the irrigation efficiency. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12938-019-0679-5) contains supplementary material, which is available to authorized users.